Zet wobec Narodowej Demokracji w przededniu I wojny światowej - Waingertner, Przemysław (Acta Universitatis Lodziensis. Folia Historica, 1998)
In this article, based on studying archival materials and press, a process of divorce between the „Zet” (League of Polish Youth „Zet”) and the Endecja (National Democracy Camp) in 1908-1914 is showed. That process appeard as a result of a disagreement in such matters like: an attitude to the independence of Poland, a vision of Polish nation, an opinion about the 1905 Revolution and its School Strike and the boycott of Russian schools. „Zet” activists constantly supported a fight for the independence, including a military action. On the other hand, the Endecja supported activity, which was based on current political and legal conditions, linking to Roman Dmowski’s political conceptions. The process of „Zet’s” leaving the Endecja structures was not simple. The Endecja opposed it, there were also some common elements of ideology and political program as well as sense of common tradition played an important part in some circles of the „Zet”. Finally, in the face of World War I the „Zet” authorities decided to support Józef Piłsudski and his military action. It can be regarded as a proof the process of divorce between the „Zet” and the Endecja was done.